Chapter Facilitating Comparative Group Work in Adult Education - Jean Francois, Emmanuel (Studies on Adult Learning and Education, 2020)
The purpose of this chapter is to describe and reflect on scholarly-based practices that can help facilitate comparative group work within the international and transnational context of adult education. The first section of this chapter situates comparative group work within the larger context of comparative adult education, followed by a focus on how to facilitate a group of diverse learners with different societal and cultural experiences. The chapter emphasiszes an outcome-based approach, describing how to set up incremental learning outcomes to enable comparative group work to be successful; a team-based approach, elaborating on coaching strategies to facilitate comparative work group; and a strength-based approach about adult learner-centered strategies for engagement, empowerment, mentoring, collaboration, fun, and accountability when facilitating comparative group work.